Unveiling the potential of Cepharanthine from plant to patient- A comprehensive review of phytochemistry, pharmacology and clinical investigations - Dobhal S.; Nandave M.; Tiwari V.; Singh M.F. (My University, 2025)
Cepharanthine (CEP), a cyclic alkaloid derived from several Stephania genus species, has been widely utilized in Japan since the 1950s to address a range of ailments. CEP is an optically active compound which belongs to the bisbenzylisoquinoline class of alkaloids and is characterized by its non-phenolic nature and solubility in ether. Renowned for its multifaceted pharmacological properties, CEP exhibits an array of beneficial effects, including antioxidative, anti-inflammatory, immunomodulatory, antitumoral, neuroprotective and antiviral actions. Notably, CEP shows promising potential in combating various cancers such as colorectal, breast, lung, prostate, liver cancer. Additionally, CEP has emerged as a compelling candidate among natural compounds under investigation for its capacity to serve as an effective anti-inflammatory agent, displaying positive outcomes both in vitro and in vivo. Consequently, its therapeutic applications in numerous inflammatory diseases hold great promise. This review provides a comprehensive overview of CEP, including its physicochemical properties, pharmacological effects, mechanisms of action, signalling pathways and therapeutic potential in cancer treatment. The effect of combination therapy of CEP with other anticancer agents has also been summarized emphasizing the potential of CEP to overcome drug resistance and radio resistance. Furthermore, this article provides a summary of novel dosage formulations that have been developed for the efficient, safe and convenient delivery of CEP. © 2024 Har Krishan Bhalla & Sons.